THE STUDY OF MELATONIN LEVELS IN THE BLOOD SERUM OF MALE RATS OF DIFFERENT AGES ON THE BACKGROUND OF DESYNCHRONOSIS - Hnatiuk, V. (World of Medicine and Biology, 2015)
Melatonin it is a hormone that synthesized in virtually all living organisms. This is one of the most evolutionarily conserved regulators compounds. The aim of our work was investigated the melatonin levels in the blood serum of male rats of all ages against background of desynchronosis. The experiment was conducted on 48 male rats aged 3, 9, 15 and 20 months, that corresponds to the human's age 14-15 (adolescence), 29-30 (adult period), 43-44 (mature early), 55-56 (mature late) respectively. Animals were divided into 8 groups (6 animals in every group): 1 – 4 groups – intact control corresponding age, that were kept under natural light without the influence of artificial light sources; 5 – 8 groups – animals that were in the lighting conditions around twenty-four hour during 14 days – desynchronosis. Determining the melatonin level in the blood serum of rats was performed on 15th day of the experiment by method of enzyme multiplied immunoassay using a set of Melatonin ELISA (IBL-International, Hamburg, Germany).Results and discussion. The studying of melatonin concentration in the serum of male rats of different age in groups of intact control showed that significant differences between levels of melatonin were absent. Fremitus between levels were in the range of 1 to 6% (p≥0,05). Wherein the lowest melatonin level was determined in rats aged 9 months – 286.8±8.93 pmol/l and 20 months – 289.4±7.13 pmol/l, that on 5-6% fewer than in rats aged 3 months, which had the highest level of melatonin – 303.4±7.57 pmol/l.Against background of desynchronosis was decreased melatonin level in all age groups significantly. The lowest level in rats aged 20 months – 192.5±19.16 pmol/l, which was on 33% lower than in the group of intact control (p=0.0008) and in the group of rats aged 9 months – 197.2±10.71 pmol/l (p=0.00008) – on 30% below to the corresponding intact control. At ages groups 3 and 15 months the decreasing was 18% (p=0.02) and 20% (p=0.02) respectively. During comparing melatonin levels between ages groups on a background of desynchronosis was determined that rats aged 9 and 20 months it was on 21% (p=0.023) and 23% (p=0.046) lower than melatonin level of rats aged 3 months and on 16% (p=0.079) and 18% (p=0.12) – rats aged 15 months.Nowadays we know that melatonin deficiency that occurs into disturbance of light status leads to a lot of diseases: tumors of different organs in old age, ulcers, diabetes and others. After receiving the dates about the decreasing of melatonin level in the blood serum of rats of different ages, we can assume that the age at which the likely increase of these diseases can be not only advanced, but also 29-30 years.Conclusions. Based on the studying was established that in male rats against background of disynchronosis decreasing the melatonin level in blood serum in all age groups significantly. The highest decreasing occurs in the age group 9 months and 20 months that corresponding to the human's age 29-30 and 55-56 years.
Keywords: melatonin; desynchronosis; male rats; age